Scale effects of graphene and graphene oxide coatings on pool boiling enhancement mechanisms. (June 2017) - Jaikumar, Arvind; Gupta, Anju; Kandlikar, Satish G.; Yang, Chien-Yuh; Su, Ching-Yuan
Highlights: Nano and microscale effects of graphene oxide surfaces on pool boiling performance. Spectral and morphological characterization of graphene oxide surfaces. Evaluation of scale induced pool boiling enhancement mechanisms. Wettability and enhanced evaporation through microlayer partitioning mechanisms. Abstract: Surface modifications through conductive carbon based coatings, such as graphene (G) and graphene oxide (GO) are studied to enhance the pool boiling heat transfer performance. In this study, four different mechanisms for G/GO coatings in the nanoscale and microscale were evaluated. We report the results of specifically designed experiments and discuss the effects of (i) thermal conductivity of graphene films, (ii) wettability, (iii) contact angle hysteresis, and (iv) morphological effects. For the nanoscale coatings, an atmospheric pressure chemical vapor deposition (APCVD) process was used to exercise control over the number of layers. For these samples, it was seen that the thermal conductivity and wettability through increased wickability were not contributing factors, but the large contact angle hysteresis (∼50°) was seen as a possible mechanism. The microscale coatings were developed through a dip-coating technique. Morphological features were generated by varying the dip-coating duration between 2 and 20 min. Pool boiling tests were conducted with distilled water at atmospheric pressure which resulted in a maximum CHF of 192 W/cm 2 corresponding to the sample with ridge microstructures. In addition to the contact angle hysteresis in these samples, the roughness was seen to be responsible for the CHF enhancement with longer dip-coating durations (in excess of 5 min) which was further verified by using a roughness based CHF model. In the case of shorter duration coatings, the unique ridge microstructures enhanced the microlayer evaporation. Bubble growth rates in the initial inertia controlled region were obtained to provide further details on the heat transfer mechanism. In summary, contact angle hysteresis, roughness, and evaporation from ridge partitioned microlayer were identified as the three mechanisms associated with nanoscale and microscale G/GO coated surfaces.